Close neighbors, not intruders: investigating the role of tank bromeliads in shaping faunal microbiomes - Rodolfo Martínez-Mota; Antonio Acini Vásquez-Aguilar; Dolores Hernández-Rodríguez; Emilio A. Suárez-Domínguez; Thorsten Krömer (PeerJ)
Background Tropical montane cloud forests contain high levels of epiphyte diversity. Epiphytic tank bromeliads play an important role in the functioning of these ecosystems and provide a microhabitat for many species of invertebrates. Microbial ecology theory suggests that the environment serves as a source of microbes for animals, but the contribution of this factor to the composition of an animal microbiome varies. In this study, we examined the extent to which tank bromeliads (Tillandsia multicaulis) serve as a source of microbes for two species of fly larvae in a cloud forest fragment in central Veracruz, Mexico. Methods We used 16S rRNA sequencing to characterize the bacterial communities in the organic matter within bromeliad tanks and in the whole bodies (surface and gut) of larvae from two fly taxa (Austrophorocera sp., Tachinidae, and Copestylum sp., Syrphidae) that inhabit these bromeliads. To assess the contribution of bromeliads to the microbiome of the fly larvae, we conducted fast expectation-maximization microbial source tracking (FEAST) analysis. Results The bacterial communities in bromeliad tanks were primarily composed of Pseudomonadota, Acidobacteriota, Bacteroidota, Verrucomicrobiota, and Spirochaetota. Similarly, communities of the fly larvae contained Pseudomonadota, Bacteroidota, Bacillota, and Actinomycetota. Bromeliad tanks exhibited the highest bacterial richness, followed by Copestylum and Austrophorocera larvae. Beta diversity analyses indicated that bacterial communities clustered by species. We found a modest contribution of bromeliads to the fly microbiome, with nearly 30% of the larvae microbiome traced to the organic matter deposited in the tanks. Conclusions Our data suggest that the microbiome of flies, which inhabit tank bromeliads during their larval stage, is nourished to some extent by the bacterial communities present in the organic matter within the tank.